Settlement of Debtors in Default in Credit Agreements with Movable Property Guarantees - Maharani, Aulia (Jurnal Scientia Indonesia, 2021)
An agreement between two or more people is referred to as an agreement. Agreement is something that often happens in society. There are various types of agreements, one of which is a credit agreement, this credit agreement can occur between a debtor and a creditor so as to create a debt-debt relationship, where the debtor is obliged to repay the loan granted by the creditor, based on the terms and conditions agreed upon by the parties. However, sometimes there are conditions where the debtor cannot carry out the obligations specified in the agreement so that collateral is needed in this case movable objects. This article aims to discuss the settlement if the debtor defaults in the credit agreement by using movable objects as collateral. And the method used in this article is a qualitative descriptive method with a normative juridical approach. The results of the discussion on the settlement of defaulting debtors in credit agreements with movable property guarantees, namely through litigation in the form of filing a lawsuit to the district court in accordance with the provisions of civil procedural law, or requests for execution and settlement through the state receivables affairs committee for loans involving state assets or through non-litigation, namely settlement of legal cases carried out outside the court such as mediation, consultation, negotiation, and conciliation.